Development of an advanced nano-satellite VELOX-I - Study of high dynamic range CMOS image sensor and pixel design - Ho, Evan Wei Li. (2013)
The Undergraduate Satellite Programme is a real-world engineering project participated by engineering students, school staff, and professors to build and launch Singapore’s first home developed satellites. The Velox-I nano-satellite is scheduled to be launched next and one of its subsystems is the camera payload. The basic building block of a camera system is the pixels located within the image sensor, which converts optical signals into electrical signals. One quality factor to consider is the Dynamic Range of the pixel, which determines the amount of detail the pixel can provide at different illuminated conditions.